Perbaikan Sistem Kerja Pada Bagian Komponen Di PT. XYZ - Christhopher Gilbert (Jurnal Titra, 2019)
PT. XYZ is an international company that moves in production. PT. XYZ main production is footwear. Footwear that PT. XYZ produce is divided into two, which is shoes and sandals. In producing its footwear, PT. XYZ uses make to stock system. PT. XYZ main area production is divided into three area, shoes production area, upper production area, and component production area. Improvement is only applied on component area, using Left and Right Hand Diagram and analyzing items placement on work station. Analysis was conducted to get a better proposal of better Left and Right Hand Diagram, and  better items placement on work station. Measurements resulted a reduction in component area cycle time of 1.64 minutes or 98.4 second.